If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 11v + 4x + -1v = 0 Reorder the terms: X + 11v + -1v + 4x = 0 Combine like terms: 11v + -1v = 10v X + 10v + 4x = 0 Solving X + 10v + 4x = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-10v' to each side of the equation. X + 10v + -10v + 4x = 0 + -10v Combine like terms: 10v + -10v = 0 X + 0 + 4x = 0 + -10v X + 4x = 0 + -10v Remove the zero: X + 4x = -10v Add '-4x' to each side of the equation. X + 4x + -4x = -10v + -4x Combine like terms: 4x + -4x = 0 X + 0 = -10v + -4x X = -10v + -4x Simplifying X = -10v + -4x
| 79-x=1 | | 60-x=41 | | 11+5z=6 | | 4=87-y | | (4y^2)+3y-1=0 | | (5x-9)(9x+8)=0 | | 90-m=1 | | 96-p=63 | | (9k^2)-9k+2=0 | | 26t+5a-4t-2= | | r-28=33 | | 84-v=29 | | (7z^2)-10z+3=0 | | 71-x=22 | | 8x-5=2x+11 | | 47=c-31 | | X^2+10x-11x=0 | | w/-6=-9 | | a-16=12 | | 45=79-h | | 7c+3=17 | | 45=54-d | | 47=54-d | | (8Z^2)+14z+5=0 | | 62=81-r | | 12i+7r-14i= | | 12i+7r-14y= | | 3t+1=7t | | 6a^2-13a+15=6a | | 95-b=73 | | 0=2x^2-20+50 | | f-25=25 |